The Effectiveness of Aerobic Exercise, Strength Training, and HIIT in Obesity Management: Literature Review - Danutirta, Putra; Dyana Kristi, Priska; Pribadi, Agus (Indonesian Conditioning Coaches, 2025)
Excessive body fat buildup brought on by an imbalance between energy intake and expenditure is the hallmark of obesity, which raises a number of metabolic and cardiovascular risks. The effectiveness of aerobic exercise, resistance training, and High-Intensity Interval Training (HIIT) in the management of obesity is the main emphasis of this study, which employs a literature review strategy by looking at papers from PubMed and Google Scholar published between 2015 and 2025. The analysis's findings demonstrate the effectiveness of aerobic exercise in lowering waist circumference, body fat percentage, and body weight. Resistance training is crucial for lowering visceral fat, maintaining basal metabolism, and gaining lean mass. While HIIT offers a more effective training period, it significantly reduces body fat and improves VO2peak. All things considered, the three forms of exercise have complimentary advantages and work best when combined in a planned, activity-based obesity control program.